The Impact Of Technology Mastery On Students' Effectiveness Of The Spreading Of The Great Commandment At Stt Kerusso - Kezia Verena (International Perspectives in Christian Education and Philosophy, 2024)
This study examines the impact of technology proficiency among students on the effectiveness of spreading the Great Commission at Sekolah Tinggi Teologi (STT) Kerusso. The urgency of this research lies in the rapid advancement of digital technology, which offers various tools and platforms that can support evangelism missions. Technology proficiency among STT students is crucial as it enables them to expand their reach and enhance the efficiency of delivering the Gospel message in this digital era. The primary objective of this research is to identify the extent to which students' technology proficiency affects their effectiveness in carrying out evangelism missions and to explore ways in which technology can be better integrated into evangelism strategies at STT Kerusso. This study employs a qualitative method using in-depth interviews and case studies. Interviews were conducted with students and faculty members of STT Kerusso who have experience using technology for evangelism. The collected data were analyzed descriptively to identify relevant patterns and themes. The findings of this study are expected to provide new insights for theological education institutions on the importance of integrating technology into the curriculum and mission activities to maximize the spread of the Great Commission.